2013
DOI: 10.1111/ijd.12167
|View full text |Cite
|
Sign up to set email alerts
|

The effect of domestic laundry processes on fungal contamination of socks

Abstract: Tinea pedis is a common chronic skin disease. The role of contaminated clothes as a possible source of reinfection is not fully understood. This study was conducted to evaluate the efficacy of domestic laundering at different temperatures in the eradication of fungal pathogens from contaminated socks. Samples from 81 socks worn by patients suffering from tinea pedis underwent domestic laundering at either 40 °C or 60 °C. The socks were dried at room temperature; fungal cultures were taken from two samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…For nearly all tested microbial strains, the LR at 30 °C and 40 °C were very similar, independent from the use of AOB or an increased main wash duration. This confirms the findings of studies using a domestic washing machine and T. mentagrophytes as a fungal test strain (Amichai et al, ; Bloomfield et al, ; Bockmühl, , ; Honisch et al, , ).…”
Section: Resultssupporting
confidence: 87%
“…For nearly all tested microbial strains, the LR at 30 °C and 40 °C were very similar, independent from the use of AOB or an increased main wash duration. This confirms the findings of studies using a domestic washing machine and T. mentagrophytes as a fungal test strain (Amichai et al, ; Bloomfield et al, ; Bockmühl, , ; Honisch et al, , ).…”
Section: Resultssupporting
confidence: 87%
“…36,39 Successful sanitization using this sanitization method was heavily dependent on the textile used (eg, woolen socks versus broad-mesh nylon socks) and the causal strain (eg, yeasts versus Aspergillus molds) involved. 6,33 In contrast, in six eligible studies, laundering was found to be a sufficient sanitization method. 16,32,34,35,37,38 In these studies, the sanitization abilities of the laundering process was still impacted by the causal strain; however, dermatophyte colonies (T rubrum and T interdigitale) were still reduced and/or eliminated after laundering.…”
Section: Launderingmentioning
confidence: 85%
“…Tanaka et al, 2006 16 Boiling water, cold water, and wiping methods Ghannoum et al, 2012 4 SteriShoe accompanied by a cycle of UVC irradiation Gupta and Brintnell, 2013 14 Ozone application with a drying/ heating component Cronin et al, 2014 11 UV irradiation Messina et al, 2015 5 Cyberclean, a sanitizing putty Abbreviation: PCP, pentachlorophenate. 26,27,47 Bactericides and fungicides English et al, 1967 32 Laundering Broughton, 1955 6 Laundering Tanaka et al, 2006 16 Laundering with or without soap and sock position Borkow and Mellibovsky, 2012 48 Copper oxide Amichai et al, 2013 33 Laundering at 408C or 608C Amichai et al, 2014 22 Sun exposure 36 Laundering and sanitization measures a Jung et al, 2007 37 Silver ion laundry machine He et al, 2008 38 Silver and light irradiation laundry machine Borkow and Gabbay, 2008 29 Copper oxide…”
Section: Mothballsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that mechanical agitation in either hot (60°C) or cold (30°C) water can decrease the fungal load. 4,5 Studies on the decontamination of laundry items exposed to M canis are lacking. The purpose of this study was therefore to determine the effectiveness of home laundry practices for the decontamination of M canisexposed fabrics.…”
Section: Introductionmentioning
confidence: 99%